Sonographic assessment of fetal occiput position during the second stage of labor: how reliable is the transperineal approach?. (2nd November 2015) - Ghi, T.; Bellussi, F.; Eggebø, T.; Tondi, F.; Pacella, G.; Salsi, G.; Cariello, L.; Piastra, A.; Youssef, A.; Pilu, G.; Rizzo, N.
Abstract: Objective : To compare the accuracy of transperineal (TP) ultrasound with transabdominal (TA) approach in the sonographic assessment of fetal occiput position during the second stage of labour. Methods : A series of low-risk women at term attending the labour ward of three university hospitals were prospectively recruited for the purpose of this study. During the second stage of labor patients were evaluated first by TP and than by TA ultrasound to determine the fetal position. The occiput position was labelled as DOA (direct occiput anterior), ROA (right occiput anterior), LOA (left occiput anterior), DOP (direct occiput posterior), ROP (right occiput posterior), LOP (left occiput posterior), ROT (right occuput transverse) and LOT (left occiput transverse). The agreement between the two techniques was assessed. Results : Overall 80 patients were recruited in the study group. Ultrasound examination was performed at 21(±8) minutes from the beginning of the active pushing. The ultrasound findings of the fetal occiput position were recorded. In all cases TA ultrasound confirmed the fetal occiput position as determined at TP approach except in one case of ROA that had been recorded as ROT using TP ultrasound. Conclusions : Ultrasound TP examination is accurate in the diagnosis of fetal occiput position during the second stage of labor.